Anti-metabotropic glutamate receptor 5 coexistent anti-N-methyl-D-aspartate receptor encephalitis: a case report and literature review - Gu, Yixin; Xuan, Tingting; Li, Pankui; Zhou, Jing; Wang, Zhenhai (Frontiers in Immunology, 2025)
Metabotropic glutamate receptor 5 (mGluR5) antibody encephalitis is an infrequent clinical disorder, initially reported in 2011 among two patients presenting with limbic encephalitis and Hodgkin’s lymphoma. Mental and behavioral abnormalities are prevalent manifestations, accompanied by cognitive impairment, movement disorders, seizures, and other associated symptoms. In this report, we present the case of a young female patient who presented with abnormal mental behavior, seizures, and disturbances of consciousness. A cell-based assay (CBA) showed positive IgG metabotropic glutamate receptor 5 in both her serum and cerebrospinal fluid (CSF), as well as positive IgG N-methyl-D-aspartate receptor (NMDAR) in both her serum and CSF. She was diagnosed with mGluR5 overlapping NMDAR antibody encephalitis and received high-dose intravenous methylprednisolone pulse therapy and immunoglobulin therapy. Tumor screening suggested the presence of bilateral ovarian teratoma. However, unfortunately the prognosis was extremely poor. Clinical results suggested that patients with mGluR5-Abs mostly have good prognoses, excepting our case.